Agresi dan Culture of Honor di Manggarai, Nusa Tenggara Timur - Primus Domino (Fakultas Psikologi Universitas Negeri Malang, 2020)
Manggarai culture approves aggression for self-protection and self-respect, family or group called culture of honor. This culture is manifested in caci dance, sparring and belis. The attempts to injure opponents in the caci dance are carried out to preserve self respect, village honor, and group honor; Likewise, a fighting match occurs because the Manggarai people do not want the land which is their honor threatened to be taken by someone else. Other forms of culture of honor in Manggarai are the practice of belis, which shows patriarchal culture; men have a role as the main control in family and community life. This legalizes the violence committed by fathers in the family to maintain its reputation for masculinity.